2002
DOI: 10.1097/00005537-200203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Endoscopy in the Diagnosis of Early Laryngeal Cancer and Its Precursor Lesions

Abstract: Autofluorescence endoscopy facilitates the detection and delineation of precancerous lesions, carcinoma in situ, and microinvasive cancer of the larynx more accurately than clinical observation alone. Scarring, marked hyperkeratosis, and inflammation can limit the predictive value of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 16 publications
3
55
1
7
Order By: Relevance
“…In 2006, Arens and his colleagues (130) affirmed that it is not possible to detect the responsible endogenous fluorophore from the remitted autofluorescence light because it is a summation spectrum, and in thickened precancerous and cancerous mucosa (>300 µm) the light beam is not able to penetrate. On the contrary, Wang et al (116,126,128,130,238) image the high grade of heterogeneity found in our study, that could be linked the high incidence of false positive results with a still rather low Sp (80%). In fact, due to the high absorption of excitation light by haemoglobin, false positives (decreased autofluorescence with a nonmalignant histopathology) occurred more frequently in the presence of highly vascularized lesions such as telangiectasic polyps, granulation tissue, papillomas; while they were relatively common in case of scar tissue or pronounced local inflammatory reactions of the mucosa.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…In 2006, Arens and his colleagues (130) affirmed that it is not possible to detect the responsible endogenous fluorophore from the remitted autofluorescence light because it is a summation spectrum, and in thickened precancerous and cancerous mucosa (>300 µm) the light beam is not able to penetrate. On the contrary, Wang et al (116,126,128,130,238) image the high grade of heterogeneity found in our study, that could be linked the high incidence of false positive results with a still rather low Sp (80%). In fact, due to the high absorption of excitation light by haemoglobin, false positives (decreased autofluorescence with a nonmalignant histopathology) occurred more frequently in the presence of highly vascularized lesions such as telangiectasic polyps, granulation tissue, papillomas; while they were relatively common in case of scar tissue or pronounced local inflammatory reactions of the mucosa.…”
contrasting
confidence: 91%
“…Fluorophores are present at different concentrations in healthy and neoplastic laryngeal mucosa; for example, nicotinamide adenine dinucleotide (NADH) predominates within neoplastic cells in its dehydrogenated nonfluorescent form (113,114). Several fluorophores are normally found within laryngeal mucosa including prophyrins, elastin, collagen, and NADH (115,116). Because each fluorophore has a specific wavelength at which its electrons are maximally excited, it is possible to target specific fluorophores, such as NADH, using an illuminating light of a single wavelength (monochromatic).…”
Section: Autofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…In 90% of cases carcinomas develop from precancerous epithelial lesions [8]. Prompt treatment after an early diagnosis is capable to prevent the development of an invasive neoplasm and the consequent recourse to more invasive laryngeal surgery [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods were introduced to improve the accuracy of sampling during microlaryngoscopy. Among these technologies, "optical" biopsy (Kothe et al, 2005), rigid endoscopy (Kawaida et al, 1998), contact endoscopy (Andrea et al, 1995a;Andrea et al, 1995b;Arens et al, 2003;Carriero et al, 2000;Cikojevic et al, 2008;Wardrop et al, 2000), autofluorescence endoscopy (Delank et al, 2000;Gillenwater et al, 1998;Harries et al, 1995;Malzahn et al, 2002), aminolevulinic acidinduced fluorescence (Arens et al, 2007;Csanady et al, 2004;Gillenwater et al, 1998) and optical coherence tomography (OCT) (Armstrong et al, 2006;Lüerßen et al, 2006;Wong et al, 2005) should be noted. Except for the latter method, all technologies mentioned mainly visualize macroscopically suspect lesions of the larynx.…”
Section: Introductionmentioning
confidence: 99%